Novel intermicrobial molecular interaction: Pseudomonas aeruginosa Quinolone Signal (PQS) modulates Aspergillus fumigatus response to iron. Issue 1 (22nd November 2019) - Nazik, Hasan; Sass, Gabriele; Ansari, Shajia R.; Ertekin, Reyhan; Haas, Hubertus; Déziel, Eric; Stevens, David A.
Abstract : Pseudomonas aeruginosa (Pa) and Aspergillus fumigatus (Af), the commonest bacterium and fungus in compromised host airways, compete for iron (Fe). The Pseudomonas quinolone signal (PQS), a Pa quorum sensing molecule, also chelates Fe, and delivers Fe to the Pa cell membrane using Pa siderophores. In models of Af biofilm formation or preformed biofilms, PQS inhibited Af in a low Fe environment. AfΔ sidA (mutant unable to produce siderophores) biofilm was more sensitive to PQS inhibition than wild-type (WT), as was planktonic AfΔ sidA growth. PQS decreased WT Af growth on agar. All these inhibitory actions were reversed by Fe. The Pa siderophore pyoverdin, or Af siderophore inhibitor celastrol, act cooperatively with PQS in Af inhibition. These findings all indicate PQS inhibition is owing to Fe chelation. Remarkably, in high Fe environments, PQS enhanced Af biofilm at 1/100 to 1/2000 Fe concentration required for Fe alone to enhance. Planktonic Af growth, and on agar, Af conidiation, were also enhanced by PQS+Fe compared to Fe alone. In contrast, neither AfΔ sidA biofilm, nor planktonic AfΔ sidA, were enhanced by PQS-Fe compared to Fe. When Af siderophore ferricrocin (FC), +PQS, were added to AfΔ sidA, Af was then boosted more than by FC alone. Moreover, FC+PQS+Fe boosted AfΔ sidA more than Fe, FC, FC+Fe, PQS+FC or PQS+Fe. Thus PQS-Fe maximal stimulation requires Af siderophores. PQS inhibits Af via chelation under low Fe conditions. In a high Fe environment, PQS paradoxically stimulates Af efficiently, and this involves Af siderophores. PQS production by Pa could stimulate Af in cystic fibrosis airways, where Fe homeostasis is altered and Fe levels increase, supporting fungal growth.